Creative Accounting and Electoral Motives: Evidence from OECD Countries - Markus Reischmann (ifo Institute - Leibniz Institute for Economic Research at the University of Munich, 2015)
Using an unbalanced panel of 27 OECD countries over the period 1970–2011, I examinewhether electoral motives influenced creative accounting. Governments engage in“below-the-line” operations, such as transactions in financial assets, that do not show upin the deficit figures but give rise to changes in debt. I use the difference between thechange in public debt and the deficit (stock-flow adjustment) to measure creativeaccounting. The results suggest that governments strategically engaged in creativeaccounting before regular elections so as to sugarcoat the budget balance. I also providean overview of government interventions that gave rise to large stock-flow adjustments.
Keywords: C23; D72; E62; H61; H62; H63; P16; 330; Stock-flow adjustments; creative accounting; public debt; political business cycles